1998
DOI: 10.1016/s0266-7681(98)80214-3
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Versus Operative Treatment for Kienböck’s Disease

Abstract: In this retrospective study on Kienböck's disease, a comparison was made between 21 cases operated on by various techniques and 22 cases treated conservatively, with a mean follow-up of 65 months. Operative management of the disease did not show any superiority over conservative treatment. Moreover, surgery was responsible for a loss of mobility of 24%, and for a change in social activities in about a quarter of the patients, while grip strength was only slightly improved. Surgical indications for Kienböck's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 11 publications
2
39
0
4
Order By: Relevance
“…The etiology and pathogenesis of the disease are still uncertain, but several mechanical, vascular, and metabolic factors have been proposed [4,5,11,12,18]. The natural history of Kienböck is incompletely understood [3]. Progression of lunate osteonecrosis can ultimately lead to collapse and fragmentation of the diseased bone with or without secondary distortion of the carpal alignment [2].…”
Section: Introductionmentioning
confidence: 99%
“…The etiology and pathogenesis of the disease are still uncertain, but several mechanical, vascular, and metabolic factors have been proposed [4,5,11,12,18]. The natural history of Kienböck is incompletely understood [3]. Progression of lunate osteonecrosis can ultimately lead to collapse and fragmentation of the diseased bone with or without secondary distortion of the carpal alignment [2].…”
Section: Introductionmentioning
confidence: 99%
“…stages I-IIIa), the severity of radiological changes in the lunate does not always correlate with the symptoms. (10,11) There are various treatment modalities that address the different pathologies of this disease. A recent meta-analysis, which evaluated the various treatment modalities for Kienböck's disease, showed that subjective pain improved regardless of treatment type, whereas objective improvement in grip strength and range of movement occurred only in patients who received either joint levelling surgeries or VBG, and not in those who had nonsurgical treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory results also exist in comparing surgical and nonsurgical treatments. Delaere and associates found comparable outcomes with surgically treated patients, operated using various techniques, and conservatively treated with a mean of 5-year follow-up [5]. Salmon and colleagues, however, found that surgically treated patients (radial shortening) with stage II and III disease experienced less pain and demonstrated superior grip strength than their conservatively treated counterparts at a mean follow-up of 3.6 years [18].…”
Section: Discussionmentioning
confidence: 99%